2019
DOI: 10.1002/jcla.23034
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α7 is overexpressed and correlates with higher pathological grade, increased T stage, advanced TNM stage as well as worse survival in clear cell renal cell carcinoma patients: A retrospective study

Abstract: Objective This study aimed to explore the association of integrin α7 with clinicopathological characteristics and overall survival (OS) in clear cell renal cell carcinoma (ccRCC) patients. Methods 179 ccRCC patients who underwent nephrectomy were included in this retrospective study. Tumor tissue and paired adjacent tissue specimens of patients were obtained. Immunohistochemistry assay was performed to detect integrin α7 expression. OS was calculated with the median follow‐up duration of 91.0 months (range: 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…7 ITGA7, CD133, and ALDH1 mediate the CSC properties in multiple carcinomas. 9,[11][12][13][14]22,24,29,30 Therefore, overexpression of ITGA7, CD133, and ALDH1 might be correlated with poor differentiation in cervical cancer pathology. So far, former studies have revealed the correlation of ITGA7 expression with prognosis for various neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 ITGA7, CD133, and ALDH1 mediate the CSC properties in multiple carcinomas. 9,[11][12][13][14]22,24,29,30 Therefore, overexpression of ITGA7, CD133, and ALDH1 might be correlated with poor differentiation in cervical cancer pathology. So far, former studies have revealed the correlation of ITGA7 expression with prognosis for various neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…ITGA7 is reported to be positively linked with the activation of CSCs in multiple carcinomas including tongue SCC, esophageal SCC, renal cell carcinoma as well as non‐small‐cell lung cancer 9,11–13 . Whereas, the role of ITGA7 in regulating the stemness of cervical cancer cells thus further acting as a potential biomarker for the prognosis in cervical cancer patients remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data used to support the findings of this study are included within the article. I-Shiang Tzeng 1,2…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%
“…To handle the inflation of odds ratios in a retrospective study with a profile penalized log-likelihood approach Dear Editor, We read with great interest the paper authored by Chen et al 1 entitled "Integrin α7 is overexpressed and correlates with higher pathological grade increased T stage advanced TNM stage as well as worse survival in clear cell renal cell carcinoma patients: A retrospective study," published in January 2020 in the Journal of Clinical Laboratory Analysis. The authors aimed to explore the association of integrin α7 with clinicopathological characteristics and overall survival (OS) in patients with clear cell renal cell carcinoma (ccRCC) based on a retrospective study.…”
mentioning
confidence: 99%